Generation and age of immigration on later life cognitive performance in KHANDLE. (23rd January 2023) - Meyer, Oanh L.; Eng, Chloe W.; Ko, Michelle J.; Chan, Michelle L.; Ngo, Uyen; Gilsanz, Paola; Glymour, M. Maria; Mayeda, Elizabeth Rose; Mungas, Dan M.; Whitmer, Rachel A.
ABSTRACT: Objectives: We examined the association of generational status and age at immigration with later life cognitive outcomes in a diverse sample of Latinos and Asian Americans. Design: Baseline data were obtained from the Kaiser Healthy Aging and Diverse Life Experiences (KHANDLE) study, and a prospective cohort is initiated in 2017. Setting: Older adults in Northern California. Participants: Our cohort consisted of Asians ( n = 411) and Latinos ( n = 340) who were on average 76 years old (SD = 6.8). Measurements: We used multivariable linear regression models to estimate associations between generational status and age at immigration (collapsed into one five-level variable) with measures of verbal episodic memory, semantic memory, and executive function, adjusting for age, gender, race and ethnicity, and own- and parental education. Results: Generational status and age at immigration were associated with cognitive outcomes in a graded manner. Compared to third-generation or higher immigrants, first-generation immigration in adulthood was associated with lower semantic memory (β = −0.96; 95% CI: −1.12, −0.81) than immigration in adolescence (β = −0.68; 95% CI: −0.96, −0.41) or childhood (β = −0.28; 95% CI: −0.49, −0.06). Moreover, immigration in adulthood was associated with lower executive function (β = −0.63; 95% CI: −0.78, −0.48) than immigration in adolescence (β = −0.49; 95% CI: −0.75, −0.23). Similarly, compared to third-generation individuals, first-generation immigrants had lower executive functioning scores. Conclusions: Our study supports the notion that sociocontextual influences in early life impact later life cognitive scores. Longitudinal studies are needed to further clarify how immigration characteristics affect cognitive decline.